(3GdCHMGK hGdCSFdI Ydi QSGdI GdCeKdIs - (3SjO CMeO Hf eUWai dBdi RGOgs ((3MSjf Hf Ydi s)
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdePfH dBdi Efi cJHJ gPg GdChQGb s
(3BNQgG (B:s
(3Ch GdZGFH GdeLghd hGeQ GdMGVQ GdeLghd s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3JYbjHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdUQas